UPAYA PENINGKATAN KUALITAS SUMBER DAYA MANUSIA DI SMP ISLAMIYAH BANJAR REJO - Hadi Prayitno; Nurul Hidayati Murtafiah; Tamyis (UNISAN JURNAL, 2023)
In this research, the researcher uses qualitative methods with a naturalistic approach which shows that the implementation of research occurs naturally, as it is, in normal situations where circumstances and conditions are not manipulated, emphasizing natural descriptions. Collecting data or capturing phenomena is carried out from reasonable conditions known as "natural and natural collection". Based on data findings in the field, the professionalism of PAI teachers at SMP Islamiyah, Way Pengubuan District, Central Lampung Regency is described in pedagogical abilities; namely the teacher’s ability to prepare lesson plans, syllabus, Prota and Promissory notes, the ability to improvise learning methods and the ability to assess student learning outcomes through class-based assessments. Personality ability; illustrated by the inculcation of self-discipline and responsibility in assignments. Social ability; illustrated by good communication relationships with school principals, colleagues, parents of students and participation in social activities. While professional ability; illustrated by the ability to master the field of study seen from the educational background of teachers who have academic qualifications and teach teachers according to their expertise and majors, the ability to understand students. good professionalism. But it would be nice if the competency needs to be improved so that the quality of student output is even better.